1995
DOI: 10.1073/pnas.92.6.2333
|View full text |Cite
|
Sign up to set email alerts
|

HypB protein of Bradyrhizobium japonicum is a metal-binding GTPase capable of binding 18 divalent nickel ions per dimer.

Abstract: Bradyrhizobium japonicum hypB encodes a protein containing an extremely histidine-rich region (24 histidine residues within a 39-amino-acid stretch) and guanine nucleotide-binding domains. The product of the hypB gene was overexpressed in Escherichia coli and purified by Ni2+-charged metal chelate affinity chromatography (MCAC) in a single step. In SDS/PAGE, HypB migrated at 38 kDaslightly larger than the calculated molecular mass (32.8 kDa). Purified HypB has GTPase activity with a kcat of 0.18 min-1 and a K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 31 publications
(37 reference statements)
6
95
1
1
Order By: Relevance
“…The M. smegmatis orf1 product includes a histidine-rich region with potential nickel binding capacity in common with several other related proteins involved in processing nickel-containing enzymes; HypB of E. coli does not contain such a region, however. The histidine-rich region of Bradyrhizoboum japonicum HypB has been shown to function in nickel ion binding by deletion analysis (Fu et al, 1995). HypB of E. coli has also been shown to be a GTP-binding protein (Maier et al, 1993) and the four conserved domains of G-proteins (Bourne et al, 1991) identified; similar sequences are also found in the orf1 gene product although a threonine in the G-2 region thought to be critical is absent.…”
Section: Discussionmentioning
confidence: 99%
“…The M. smegmatis orf1 product includes a histidine-rich region with potential nickel binding capacity in common with several other related proteins involved in processing nickel-containing enzymes; HypB of E. coli does not contain such a region, however. The histidine-rich region of Bradyrhizoboum japonicum HypB has been shown to function in nickel ion binding by deletion analysis (Fu et al, 1995). HypB of E. coli has also been shown to be a GTP-binding protein (Maier et al, 1993) and the four conserved domains of G-proteins (Bourne et al, 1991) identified; similar sequences are also found in the orf1 gene product although a threonine in the G-2 region thought to be critical is absent.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, including A. eulrophus but not E. c d i , HypB proteins contain extended histidine clusters. Analyses of purified HypB of' Hradyrhizobiumjuponicum (Fu et al, 1995) and K. leguminosarum (Rey et al, 1994) revealed Ni binding to these clusters with a stoichiometry of 9 Ni and 4 Ni to each HypB monomcr, respectively. Much less is known on the function of the other hyp products.…”
Section: Discussionmentioning
confidence: 99%
“…CP: carbamoyl phosphate. present at the N terminus of HypB enables the protein to store nickel (Rey et al, 1994;Fu et al, 1995;Olson et al, 1997, Olson andMaier, 2000). In other organisms, such as E. coli or R. eutropha, the absence of this nickelstorage function has been assumed to be compensated by a highly effi cient nickel transport system (Eitinger and Mandrand-Berthelot, 2000).…”
Section: Metallocenter Assemblymentioning
confidence: 99%